2007
DOI: 10.1021/cm070602i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, and Luminescence Properties of Lanthanide Oxalatophosphonates:  Na[M3(H2O)4(C2O4)4(CH3PO3)]·2H2O (M = Nd and Pr)

Abstract: A neodymium oxalatophosphonate and its praseodymium analogue, Na[Nd3(H2O)4(C2O4)4(CH3PO3)]·2H2O and Na[Pr3(H2O)4(C2O4)4(CH3PO3)]·2H2O, have been synthesized by a hydrothermal method and characterized by single-crystal X-ray diffraction and thermogravimetric analysis. We studied the photoluminescence spectra of the Nd and Pr compounds as well as the magnetic properties of the Nd compound. The structure consists of layers built of tetramers of edge- and face-sharing NdO9 (or PrO9) polyhedra connected by oxalate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…The P-C distance is 1.791(14) Å. These distances are in good agreement with similar compounds in the literature (Legendziewicz et al, 1998; Serre et al, 2004; Song and Mao, 2005; Tang et al, 2006a; Ying and Mao, 2006; Huang et al, 2007; Liu et al, 2007; Mao, 2007). …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The P-C distance is 1.791(14) Å. These distances are in good agreement with similar compounds in the literature (Legendziewicz et al, 1998; Serre et al, 2004; Song and Mao, 2005; Tang et al, 2006a; Ying and Mao, 2006; Huang et al, 2007; Liu et al, 2007; Mao, 2007). …”
Section: Resultssupporting
confidence: 89%
“…The design and syntheses of porous lanthanide phosphonates are attractive in developing new materials with multifunctions (Song and Mao, 2005; Ying and Mao, 2006; Liu et al, 2007; Mao, 2007). The successful synthesis of the first open-framework lanthanide carboxyphosphonate Pr 4 (H 2 O) 7 (O 3 PCH 2 NC 5 H 9 COO) 4 (H 2 O), opened the way for a number of other lanthanide hybrid solids to be isolated (Massiot et al, 1997; Legendziewicz et al, 1998; Serre et al, 2004; Bauer et al, 2006; Tang et al, 2006a,b; Huang et al, 2007; Zhou et al, 2010). For example, using lanthanide chlorides and N -(carboxymethyl)iminodi(methylphosphonic acid)(H 5 cmp) a series of layered [Ln(H 2 cmp)(H 2 O)] materials [where Ln 3+ = Y 3+ , La 3+ , Pr 3+ , Nd 3+ , Sm 3+ , Eu 3+ , Gd 3+ , Tb 3+ , Dy 3+ , Ho 3+ , and Er 3+ ], and the mixed-lanthanide [(Gd 0.95 Eu 0.05 )(H 2 cmp)(H 2 O)] material, have been successfully isolated from hydrothermal synthesis as phase-pure micro-crystalline compounds, (Cunha-Silva et al, 2009) and found to be supramolecular polymorphs of the compound that was reported by Mao and co-workers (Massiot et al, 1997; Bauer et al, 2006; Tang et al, 2006b; Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed in Figure 3A that the typical Sr 2 Ga 2 GeO 7 :0.2mol%Pr 3+ sample shows characteristic emission lines in the range 450-800 nm when excited at 254 nm, which are due to the f-f transitions of Pr 3+ . 19 Particularly, the blue emissions at around 492 nm is attributed to the 3 P 0 → 3 H 4 transition and the red emission at 614 nm is ascribed to the 1 D 2 → 3 H 4 transition as shown in Figure 3B. 20 Figure 3C presents the normalized PL spectra (λ ex = 254 nm) of all Sr 2 Ga 2 GeO 7 :x%Pr 3+ samples.…”
Section: Methodsmentioning
confidence: 94%
“…Supramolecular chemistry has developed dramatically over recent decades. Numerous organometallic complexes have been designed for a number of potential applications, such as in synthetic chemistry (Sommerfeldt et al, 2008), in gas storage (Rowsell & Yaghi, 2005;Ma & Zhou, 2006), in selective absorption (Dong, Zhang et al, 2007), as luminescence materials (Wang, Ma et al, 2007;Huang et al, 2007) and as magnetic materials (Halder et al, 2002;Neville et al, 2008). Although the principles for controlling the solid structures of the target products still need to be classified and established, many rational synthetic strategies have been put forward (Dong, Jiang et al, 2007;Zhang et al, 2008).…”
Section: Commentmentioning
confidence: 99%